Components of the flipped classroom in higher education: disentangling flipping and enrichment - Bintz, Gesa; Barenberg, Jonathan; Dutke, Stephan (Frontiers in Education, 2024)
The flipped classroom (FC) model shifts the initial presentation of new content from in-class to out-of-class, while in-class time focuses on elaborating previously presented content. Although FC's benefits on learning outcomes are well-documented, the mediating processes remain unclear due to the simultaneous enrichment of learning activities in many studies. This study investigates whether merely flipping the initial presentation of new content, without additional enrichment, enhances learning outcomes.In two studies, psychology students (Study 1: N = 306; Study 2: N = 413) participated in either a non-flipped lecture series (new content presented in class) or a flipped lecture series (new content presented out-of-class via lecture recordings). Learning outcomes were assessed in terms of knowledge acquisition, knowledge application, and metacognitive monitoring.Results showed that students in the flipped classroom condition had significantly higher learning outcomes compared to those in the non-flipped condition. Specifically, the flipped approach improved knowledge acquisition, knowledge application, and metacognitive monitoring.These findings indicate that simply shifting the initial presentation of new content to an outof-class setting is sufficient to enhance learning outcomes in a flipped classroom. This study highlights the effectiveness of the flipped classroom model in fostering student learning without the need for additional enrichment activities, suggesting a structured approach to analyze the components that contribute to learning benefit from flipping the classroom.